Eksplorasi Gaya Respons Ekstrem dalam Mengisi Kuesioner - Wahyu Widhiarso (Jurnal Psikologi, 2016)
This study aimed to apply the mixture Rasch Model Analysis techniques to identify the proportion of students who possess extreme response styles when completing the questionnaire. Total 2.981 high school students from 30 cities in 15 provinces were instructed to complete questionnaires measuring self-esteem. Self-Self-Esteem Scale consists of four self-reported sub-scales using Likert's model. Analysis suggest that based on how to respond to the scale, student in this study was grouped into three classes: extreme response style class, normal class, and mixture class. These numbers of class were consistent on all four sub-scales. The proportion of students who consistently gave an extreme response on four sub-scales was 4 percent; 6 percent was on three sub-scale, 13 percent on two sub-scales and 53 percent on one sub-scale. The small percentage of students who responded consistently gave an extreme responses suggest that high-school students appropriately choose an option response that represent their trait.